EPIDEMIOLOGIC RESEARCH ON EPILEPSY IN MINSK - T. V. Dokukina; T. S. Golubeva; I. V. Matveichuk; M. V. Mahrov; V. M. Loseva; E. V. Krupenkina; S. A. Marchuk (IRBIS LLC, 2015)
the lack of proper information on the epidemiological characteristics of epilepsy results in significant shortcomings in available health care. This pharmacoepidemiological study was undertaken to improve the situation. Objective: to assess the prevalence profile and management of patients with epilepsy in Minsk based on out-patient visit data obtained in health centres subordinate to the Ministry of Health of the Republic of Belarus. Materials and methods: the epidemiological study was conducted in accordance with the ILAE 'Guidelines for epidemiologic studies on epilepsy'. Results: epilepsy incidence and prevalence were evaluated across Minsk gender- and age-based population groups. Aetiological and social aspects of epilepsy were reviewed. Out-patient visit data collected for the period from 2008 to 2012 revealed 705 patients with epilepsy. The overall epilepsy prevalence rate of the district varied from 165.2 per 100,000 population in 2008 to 275.5 per 100,000 population in 2012, while the incidence rate ranged from 36.9 per 100,000 population (in 2008) to 25.0 per 100,000 population (in 2012). The most frequently administered anti-epileptics included carbamazepine (52.9 % of patients) and valproates (31.0 % of subjects). The most commonly administered second-generation anti-epileptics were topiramate (7.1 % of patients) and lamotrigine (2.9 % of subjects). No anti-epileptics were used by 9.5 % of study subjects. Conclusions: the prevalence of epilepsy corresponds to the European Union prevalence rate. Proposals have been made concerning optimization of health care for patients with epilepsy. There is a need for large-scale pharmacoepidemiological and pharmacoeconomic studies.